AREL TO ENHANCE STUDENTS’ SPEAKING SKILLS IN DEBATING - suci rahayu nirwana; Nia Kurniawati (Universitas Suryakancana, 2018)
Speaking skill is believed as an essential part of language instruction at every level because it supports learning in multiple ways. Debate is considered as the best method to enhance students‟ speaking skills that used to construct the argument, create the logic idea, work in group, sharing knowledge and arrange the information to be delivered in debating. This is a qualitative research focuses on AREL to enhance the students‟ speaking skills in debating. The aims of this research are finding out the implementation of AREL in debating; investigating how AREL reflected on students speaking performance and revealing the obstacles faced by teacher and students in applying AREL. The research was conducted in a senior high school and involved tenth-grade students who became a delegation in each class as the candidates to compete in the debate competition in Cianjur. The instruments used for this research were observation, questionnaire, and interview. Moreover, there were stages in implementing AREL included: introducing debate of WSDC, implementing AREL (Assertion, Evidence, Reason, and Link-back), giving a stimulant, and constructing the argument. By using AREL in debating, the students became confident to speak English and got a lot of benefits from the debate not only for their speaking skills but also advancing their critical thinking. They showed their ability to explore the argument by giving a logical reason and strong evidence in order to elaborate on their argument. It was also reflected in the students speaking performance including conversational discourse, pronunciation, accuracy and fluency, affective factors, and the interaction effect. However, AREL is difficult to apply for students with insufficient ability in reading information and constructing or arranging their speech. In addition, the students were still in tenth grade and it was also such an obstacle because their speaking skill is still low. Furthermore, the students have more obstacles in their speaking skills such as memorization, anxiety, less vocabularies, and grammatical error.